Performa Produksi Ayam Broiler Menggunakan Smart Mini Closed House (Smart Pro: Production Performance of Broiler using Smart Mini Closed House (Smart Pro) - Danang Priyambodo; Pria Sembada; Gilang Ayuningtyas; Yuni Resti; Tera Fit Rayani; Inna Novianty; Sofiyanti Indirasari (Politeknik Pertanian Bogor, 2023)
Closed-house broiler chickens are one of the applications of technological developments in the livestock industry by providing an environment that is in accordance with what chickens need. Mini-closed houses are built so that small and medium farmers can raise broiler chickens in the closed houses at a minimum cost. The application of information system technology 4.0 (based on IoT) in mini-closed house enclosures enables farms to become smart farms (Smart Mini Closed House/Smart Pro). The purpose of this study was to compare the production performance of broiler chickens kept in a closed house without IoT and a closed house using IoT (Smart Pro). The IoT system is used to control temperature, humidity, and air quality in real time. Observations were made for eight periods, from August 2022 to March 2023. The observed data were analyzed descriptively. The results showed that broiler chickens reared on Smart Pro had a lower average feed consumption with a higher final weight, so the feed conversion value tended to be lower. There is no difference in the percentage of depletion or performance index between the two observations. The application of IoT technology in broiler rearing shows a tendency for an increase in production performance (final weight and feed conversion). However, it is necessary to adapt the use of new technology for human resources in controlling the IoT system so that it can be utilized optimally.